Prevalence of Death in Geriatric COVID-19 Patients with Comorbid Hypertension and/or Diabetes Mellitus in Samarinda City Hospital - Namira, Meirin Siti (Jurnal Ilmu Kesehatan, 2022)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a disease caused by a viral infection that attacks the respiratory tract which is often referred to as COVID-19. This study aims to determine the percentage of mortality prevalence in geriatric Covid-19 patients with comorbid hypertension and/or diabetes mellitus at the Samarinda City Hospital. This research method uses a non-experimental observational method with a descriptive research design. Data collection was carried out retrospectively using patient medical record data at the Samarinda City Hospital for the period March 2020-December 2021. Data analysis used the percentage of mortality prevalence in geriatric Covid-19 patients with comorbid hypertension and/or diabetes mellitus at the Samarinda Hospital using Microsoft excel. Based on the results of the study, from 70 samples of patients, the most based on gender, namely male as many as 43 patients (61%), while based on age, namely elderly elderly 60-74 years as many as 56 patients (80%). Based on the status of confirmed Covid-19 patients with comorbidities, the highest number of patients who died was 42 patients (60%). Most of the patients who died with comorbidities were found in confirmed Covid-19 patients with comorbid diabetes mellitus, namely 13 patients (44.83%). It can be concluded that the prevalence of death in geriatric COVID-19 patients with comorbid diabetes mellitus is 44.83%, hypertension is 27.59%, and hypertension with diabetes mellitus is 27.59%.